505 Late-Breaking: Ruminal Microbiota, Inflammation Cytokines, and Performance of High-yield Dairy Cows Supplemented with Saccharomyces Cerevisiae Culture. (8th October 2021) - Sun, Xiaoge; Zhang, Shu; Wang, Erdan; Lu, Na; Wang, Wei; Li, Shengli
Abstract: Dramatic increases in milk yields in recent decades have created challenges in terms of rumen pH and microbial health which ultimately impact dairy cow health. The objective of this study was to assess the effects on ruminal pH, Volatile Fatty Acid (VFA), microbiota, inflammation, and performance of high-yield dairy cows by supplementing Saccharomyces cerevisiae culture (SC). Forty Holstein cows were divided into two groups based on their milk yield, days of milk, and parity fed the same basal ration diet that did or did not contain 100 g of SC /cow per day. Individual dry matter intake (DMI) and milk yield were recorded each day. Rumen fluid and milk samples were collected after 2 hours of morning feeding at intervals of 15 days during the experiment period. The data showed that rumen pH was increased by 0.19 (P = 0.09) when SC was supplemented than no SC was provided. SC-supplemented cow consumed 0.28 kg (P < 0.05) extra DM/d. Those supplemented with SC produced 1.36 kg (P < 0.05) more milk/cow per day than did non-supplemented cows. Milk fat percentage was higher (4.11 vs. 3.96%) for cows receiving SC. There were no differences in milk protein percentage. Rumen fluid VFA concentration was not statistically affected by SC but was numerically higher acetic and lower propionic for supplemented cows. The blood of the SC group with lower inflammation cytokines and somatic cell count (SCC). SC-supplemented cows had a greater relative abundance of Prevotellaceae, Succinivibrionaceae, Fibrobacteraceae, Lactobacillaceae, and lower relative abundance of Spirochaetaceae, Methanobacteriaceae, Enterobacteriaceae than the unsupplemented cows. It had greater functions on xylanolysis, fermentation, cellulolysis in the rumen in terms of the KEGG function prediction analysis. This study demonstrated that high-yield lactation cows receiving supplemental SC produced more milk and potentially reduced the inflammation and enhanced rumen cellulolysis bacteria growth.